Bounded law of the iterated logarithm for multidimensional martingales normalized by matrices - Koval, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We investigate a bounded law of the iterated logarithm for matrix-normalized weighted sums of martingale differences in R^d. We consider the normalization of matrices inverse to the covariance matrices of these sums by square roots. This result is used for the proof of the bounded law of the iterated logarithm for martingales with arbitrary matrix normalization.